A Philosophy for a Sound Science Education Program. - Weaver, Edward K. (Education, 1959)
This article examines a philosophy for a sound science education program in the U.S. A philosophy is a representation of a preference for a way of life. And the American way of life is democracy. The American people believe then that their system of free universal compulsory education will produce intelligent effective participant-citizens. It is concluded therefore, that science education must also be a discipline of the individual for intelligent and effective participant-citizenship. This sound program of modern science education must take its central place in general education, and it must relate to the intelligent solution of the problems of the democratic society.